2014
DOI: 10.1111/nph.12699
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with soil biota shift from negative to positive when a tree species is moved outside its native range

Abstract: Summary Studies evaluating plant–soil biota interactions in both native and introduced plant ranges are rare, and thus far have lacked robust experimental designs to account for several potential confounding factors. Here, we investigated the effects of soil biota on growth of Pinus contorta, which has been introduced from Canada to Sweden. Using Swedish and Canadian soils, we conducted two glasshouse experiments. The first experiment utilized unsterilized soil from each country, with a full‐factorial cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 49 publications
6
111
3
Order By: Relevance
“…Such communities are likely not as abundant in streams where high‐quality vegetation dominates the input (Frossard et al., 2013), and this could explain the low lodgepole pine litter decomposition rates in sites with high‐quality litter input, and conversely, the positive relationship between processing rate and coniferous litter inputs. Hence, we cannot rule out that the low decomposition rate of lodgepole pine is a consequence of few microbial groups found in Swedish boreal headwaters being adapted to its litter (sensu Gundale et al., 2014; Jackrel & Wootton, 2014), rather than it merely resulting from the low quality of this litter.…”
Section: Discussionmentioning
confidence: 98%
“…Such communities are likely not as abundant in streams where high‐quality vegetation dominates the input (Frossard et al., 2013), and this could explain the low lodgepole pine litter decomposition rates in sites with high‐quality litter input, and conversely, the positive relationship between processing rate and coniferous litter inputs. Hence, we cannot rule out that the low decomposition rate of lodgepole pine is a consequence of few microbial groups found in Swedish boreal headwaters being adapted to its litter (sensu Gundale et al., 2014; Jackrel & Wootton, 2014), rather than it merely resulting from the low quality of this litter.…”
Section: Discussionmentioning
confidence: 98%
“…plant biomass difference) between two regions, Region 1 and Region 2. Therefore, our simulation is particularly relevant to recent studies that used MSS to test whether soil biota effects varied between two regions (Yang et al, 2013;Gundale et al, 2014). The true pathogenicity difference between Region 1 and Region 2 was zero: for both regions, the pathogen density distribution was that estimated from the 10 sites of Reinhart & Clay (2009) and Reinhart et al (2010a).…”
Section: Simulated Experimentsmentioning
confidence: 99%
“…all sites within a region, all plots that received the same treatment) (e.g. Van der Putten et al, 1993;Nijjer et al, 2007;Felker-Quinn et al, 2011;Pendergast et al, 2013;Rodr ıguez-Echeverr ıa et al, 2013;Yang et al, 2013;Gundale et al, 2014;Pizano et al, 2014;Hilbig & Allen, 2015;Larios & Suding, 2015) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 44 replicated Swedish experiments with both species examined by Elfving and Norgren (1993), LP survived better in most experiments and grew faster in 43 of them. The considerably higher production of LP compared to SP at SWE-64 may, however, be a result of the release of Canadian pathogens, but contributing factors could be a higher growth capacity and that the Swedish soil has shown to provide better biota for LP than the Canadian soil (Gundale et al 2014) and that the Swedish soil has lower net nitrogen immobilization than soils in Canadian LP stands (McIntosh et al 2012). In Canada the sites CAN-54 and CAN-56 were attacked by mountain pine beetle prior to measurements, and SP was considerably more damaged than LP (53% compared to 21% and 95% compared to 53% in CAN-54 and CAN-56, respectively).…”
Section: Discussion Exotic Vs Native Speciesmentioning
confidence: 99%
“…Another explanation for better success is that the biota in the new environment suits the introduced species better than where it is native. For lodgepole pine, for instance, Gundale et al (2014) showed that the Swedish soil provides better biota than the Canadian soil, and McIntosh et al (2012) found that the nitrogen availability was better in the Swedish soil than in the Canadian since the latter had higher net nitrogen immobilization. With this study we want to compare the production of lodgepole pine and Scots pine when growing as native species and as exotic species.…”
Section: Introductionmentioning
confidence: 99%